The Effectiveness of Add-on Treatment with Nutraceutical - V. T. Ivashkin; M. A. Morozova; E. A. Poluektova; O. S. Shifrin; A. G. Beniashvili; G. E. Rupchev; A. A. Alekseev; Yu. M. Poluektov; Z. A. Mamieva; A. L. Kovaleva; A. I. Ulyanin; E. A. Trush (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: evaluation of the effectiveness of the nutraceutical “Standard Zdorovia: Gastro” (“SZ Gastro”) in the treatment of patients with irritable bowel syndrome (IBS).Materials and methods. 52 patients (62 % women) diagnosed with IBS and IBS in combination with functional dyspepsia (FD) were included in the study and divided into two groups. Both groups received basic therapy according to the guidelines. The experimental group received as add-on the nutraceutical “SZ Gastro” (containing a standardized amount of menthol, gingerol and D-limonene); patients in the control group — placebo. The duration of the study was 30 days. The severity of somatic symptoms was assessed with the 7×7 questionnaire. Emotional state was assessed with the Four Dimensional Distress, Depression, Anxiety, and Somatization Questionnaire (4DSQ).Results. Patients of the experimental and control groups did not differ from each other either in terms of demographics, basic treatment, or in the severity of symptoms at the beginning of the study.The effectiveness of the treatment in the patients, who received add-on “SZ Gastro” was significantly higher than in the patients of the control group: in the control group the percentage of improvement of somatic symptoms was 22.35 %, in the experimental group it amounted to 49.18 % (χ2 = 15.9; p = 0.0001). The percentage of patients with significant decrease of emotional disturbances was also higher in the experimental group: distress (χ2 = 18.7; p = 0.0000), anxiety (χ2 = 6.9; p = 0.0097) and somatization (χ2 = 14.99; p = 0.0001). No significant side effects were registered in any of the groups.Conclusions. Add-on of nutraceutical “SZ Gastro” to basic treatment is safe and significantly increases effectiveness of the therapy in the patients with IBS and IBS in combination with PD.